(untitled) (Progressive Agriculture, 2020)
The experiment was conducted at established rose garden of Regional Agricultural Research Station, Bangladesh Agricultural Research Institute, Jashore during 2017-18 and 2018-19 winter season (November-April). The experiment was laid out in a RCBD design with three dispersed replications. Four treatment combination were as follows: T1 =IPM package-1: Mechanical control + Sticky trap (Blue and White) + weekly spray of Azadirechtin (Bio-neem plus 1EC) @ 1.0ml/L of water, T2 = IPM package-2: Mechanical control+ Sticky trap (Blue and White)+ spray of Thiamethoxam 20% (Virtako 40SC) @ 1.5 ml/L of water, T3 = IPM package-3: Mechanical control+ Sticky trap (Blue and White)+ weekly spray Chlorphenapyr (Intrepid 10EC) @ 1 ml/L of water and T4 = Farmers practice: weekly spray Imidacloprid (Imitaf 20SL) @ 0.5ml/L of water. For mechanical control hand picking was done and harmful insect also classified as the most direct and the quickest way to remove clearly visible pests. Two color stiky trap (white and blue) were set up in each line. The lowest number of rose thrips was found in IPM package 2 (6.36 in 2017-18 and 3.03 in 2018-19) and highest in farmer’s practices (14.36 in 2017-18 and 12.40 in 2018-19). The lowest percent flower infestation of rose was recorded in IPM package 2 (9.98 to 17%) and the highest in Farmers practice (19.72 to 32.66%). The highest yield (864000 no./ha in 2017-18 and 535932 no./ha) was recorded from IPM package 2 and the lowest in farmers practice (438750 no./ha in 2017-18 and 388857 no./ha). The results revealed the highest MBCR was observed in IPM package-2 (Mechanical control+ Sticky trap (Blue and White) + spray of Thiamethoxam 20% (Virtako 40SC) @ 1.5 ml/L of water.) treated plot (17.2 to 49.7) in both the year. Finally, it may be recommended that IPM package 2 is very much effective to control thrips of rose as well as high yield and more economic return. Progressive Agriculture 31 (2): 89-93, 2020